Identification of polystyrene degrading bacteria and potential enzyme action from zophobas morio for improvement and sustainable biodegradation of waste - Tan, Kian Meng (2021)
Polystyrene (PS) is a widely used petroleum-based plastic polymer. However, it is recalcitrant towards degradation and expected to remain longer in the environment which leads to a major waste problem. Moreover, conventional PS disposal and waste management consume massive amounts of chemicals and energy which have deleterious effects on the environment. Therefore, the aim of this research is to explore an alternative approach for PS biodegradation by identifying PS-degrading bacteria and the potential enzyme action isolated from the gut of PS feeding insect, Zophobas morio. The bacteria that capable of degrading PS was isolated and presumed identified and characterised as Bacillus megaterium. The viability and metabolic activity of Bacillus megaterium to utilise PS as sole carbon source were validated through indicator redox probe 2,3,5-triphenyltetrazolium chloride. Biodegradability of Bacillus megaterium corroborated by biofilm quantification, FESEM and FTIR analysis. Biofilm formed and morphological changes induced by degradation were clearly viewed via FESEM and the chemical bonds alteration was detected by FTIR analysis. The expressed PDE were profiled with SDS-PAGE and the three most visible bands were obtained at 20, 45 and 60 kDa. The protein sequencing results revealed the 20 kDa protein (Isochorismatase), 45 and 60 kDa (insignificant matches). The de novo sequencing of 60 kDa protein showed similarity to trypsin (Bos Taurus), whilst BLAST results revealed that it is a serine hydrolase enzyme. In summary, the 60 kDa protein is a multi-domain protein, with one domain functioning identified as a hydrolase. The whole protein is a hypothetical protein, with no annotated function. Thus, the results revealed unidentified, perhaps novel protein. Furthermore, PS enzymatic degraded products were identified through GC/MS analysis as part of the complementary study. The conversion pathways of PS to various aromatic and non-aromatic compounds were also proposed. The findings of this research provide insight into PS biodegradation and its potential application in waste management and polymer industries, thus encouraging the use of green and sustainable technology.